Experiences of Academic Engagement and Classroom Community in Learning Communities - Saucier, Donald; Priest, Kerry; Eiselein, Gregory; Miller, Stuart; Martens, Amanda (Kansas State University. K-State First., 2015)
Do learning communities increase experiences of academic engagement and classroom community? If so, do these effects generalize to other classes? In Study 1, the presenters assessed students’ experiences of classroom community from the beginning to the end of the semester. In Study 2, they assessed students’ experiences of classroom community and academic engagement in learning community courses, compared to their experiences in a large introductory course, and to the experiences of other students in the large introductory course who were not in learning communities. This session provides insight into experiences of academic engagement and classroom community both within and beyond learning communities.
Keywords: Critical thinking; Communication skills; Community building; Application of learning; Living-learning communities; Learning communities; Presentations (communicative events)